"Rapid Detection of Pneumocystis Carini in Spiratory Specimens of Rats by Calcofluor White Staining" - M Mohebali; M Mirbakhsh; H Keshavarz (Iranian Journal of Public Health, 2002)
The present study was carried out for evaluation of calcoflour white staining (CWS) as a rapid method for detection of Pneumocystis carinii in respiratory specimens of rats as an animal model for human infection. A total of 35 Spraque – Dawley rats were divided into two groups. Group1 (20 rats) received increasing doses of dexamethasone subcutaneously, and Group 2(15 rats)as control group that received no immunosuppressive drugs. After immunosuppressant, all of the rats were killed and necropsy was performed. Broncho-alveolar lavage (BAL) and impression smears from the lungs prepared and stained by CWS .The results were compared with a few standard staining methods which have already been used for P.carinii. The calcofluor white staining was found to have more validity (sensitivity and specificity) than other staining methods such as Geimsa , Modified Geimsa and Toluidine blue O ( TBO ) .The study showed the CWS to be more valid , faster and easier to perform for detecting of P. carinii rganism.